Gender dynamics in non-hybrid cererals and legumes in Ethiopia and Uganda - Njuguna-Mungai, Esther (International Crops Research Institute for the Semi-Arid Tropics, 2017)
Presented by Esther Njuguna (ICRISAT), as part of the Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 7-8 December 2017